Three-Phase Diode Rectifiers with Low Harmonics Current Injection Methods - Pejovic, Predrag. (Power Electronics and Power Systems,, 2007)
In this book, principles of the current injection are discussed first. This discussion is followed by an analysis of various magnetic current injection devices. The third harmonic current injection is discussed next, and several current injection networks are analyzed. The optimal current injection is the topic that follows, and the requirements imposed to the current injection network in order to provide the optimal current injection are derived. Several current injection networks that provide the optimal current injection are proposed, and some parasitic effects are discussed. Recovery of the power taken by the current injection networks is analyzed, and two types of passive resistance emulators are analyzed in detail, the current-loaded resistance emulator, and the voltage-loaded resistance emulator. Avoiding the inductor of the current injection network results in mutipulse operation of the current injection based rectifiers with passive resistance emulators, which is discussed next. In a separate chapter, a different current injection device based on three bi-directional semiconductor switches is presented, and previously derived results are generalized for this special type of current injection device. At last, the results are generalized to three-phase full-bridge thyristor rectifiers. Essentially, the book presents digested results of numerous research papers published in the last fifteen years in the area of current injection based rectifiers. The book may be of interest for the people involved in design of low-harmonic three-phase rectifiers, and the people involved in research in this area.